The role of procurement quality controls in procurement performance in the energy sector in Zimbabwe. Issue 1 (1st January 2019) - Munyimi, Tinotenda Fredrick
Abstract: Procurement performance is a rapidly developing area of research. Many companies are trying to find tools for optimising procurement performance measures in response to turbulent business markets and for efficiently controlling their business activities. No empirical research has been conducted in the role of procurement quality controls in procurement performance of the energy sector. This research intends to make a contribution to existing procurement literature by measuring the role frolicked by procurement quality controls in procurement performance in the energy sector. The major objective was to: establish the role of value engineering, variety reduction, standardisation and specifications in procurement performance. A cross-sectional survey of energy companies was used in this research. This research targeted practising procurement practitioners working in companies in the energy sector. Purposive sampling method was utilised to select energy companies; however, simple random sampling method was utilised to select seventy 70 practising procurement practitioners from the entire population of eighty five 85 practising procurement practitioners of all energy companies. This research is based on closed-ended questions to procurement managers, procurement officers, buyers, procurement clerks and open-ended interviews for procurement managers only. The data were described and analysed through the use of Statistical Package for Social Sciences (SPSS) software (Version 20), and the findings were presented in tables. Analysis for variance (ANOVA) and regression analysis were utilised to test the hypothesis. The procurement quality controls clustered into four categories: value engineering, variety reduction, standardisation and specifications were found to have a positive significant correlation in procurement performance. This research finding recommends that practicing procurement practitioners in the energy sector should move towards these procurement quality controls to upsurge procurement performance in order to reinforce its position at the board of directors. Further, important concerns such as why quality consciousness in procurement, creating corporate advantage through procurement quality controls and understanding the effect of procurement quality controls in the correlation between procurement performance and firm performance are some of the other areas worth researching in the future.